The effect of an interleukin receptor antagonist (IL-1ra) on colonocyte eicosanoid release - G. S. Smith; C. Rieckenberg; W. E. Longo; D. L. Kaminski; J. E. Mazuski; Y. Deshpande; T. A. Miller (Hindawi Limited, 1996)
We investigated whether an interleukin 1 receptor antagonist (IL-1ra) altered cellular release of prostanoids and leukotrienes in a transformed colonic cell line (CACO-2) in the presence of proinflammatory stimuli. Cellular inflammation was induced by treatment with lipopolysaccharide (LPS) or the cytokine, interleukin 1 beta (IL-1β). In a separate set of experiments, cells were pretreated with IL-1ra prior to exposure to LPS or IL-1β. Prostaglandin E2 and leukotriene B4 (LTB4) levels were quantified by ELISA assays. Both LPS and IL-1β exposure were noted to stimulate cellular PGE2 release, a response which was significantly inhibited by IL-1ra treatment. Either stimulant when administered alone failed to stimulate release of LTB4. When administered after IL-1ra pretreatment however, both stimuli caused a significant increase in LTB4 release. These results suggest that a cytokine receptor antagonist can selectively influence eicosanoid production in this cell line. Furthermore, this study suggests that a IL-1ra may have a future clinical role in the treatment of inflammatory disorders of the colon which are intimately linked to enhanced eicosanoid synthesis.